Identification of the elastic characteristics of a composite material based on the results of tests for the stability of panels made from it - R.A. Kayumov; B.F. Tazyukov; I.Z. Muhamedova; F.R. Shakirzyanov (Учёные записки Казанского университета: Серия Физико-математические науки)
The problem of identifying the mechanical characteristics of a fibrous compo site material (FCM), from which cylindrical panels or pre-curved plates are made by superposition at an angle to the edge, has been considered. The problem has been solved using the analysis of the results of the tests of structures with bringing them to the loss of bearing capacity due to loss of stability.